Nonconformist theology in the twentieth century - Sell, Alan P.F., (Alan Philip Frederick), 1935- (Milton Keynes, UK : Paternoster, 2006)
A comprehensive study of the theology, produced within the major Nonconformist traditions during the twentieth century.
At head of title: The Didsbury Lectures 2006.
Includes bibliographical references and indexes.
Keywords: Dissenters, Religious -- England -- History -- 20th century; Theology, doctrinal, -- history -- 20th century; Dissent